Kajian Aspek Reproduksi Ikan Tongkol (Auxis thazard) yang Didaratkan di Pantai Segara Kusamba, Bali pada Musim Barat - Jayanti, Ni Luh Sari Risna Dwi; Perwira, Ima Yudha; Pratiwi, Made Ayu (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Frigate Tuna is one of the most economical catched fish at the Segara Beach, Kusamba. This study was aimed to observe the reproduction aspect of Frigate Tuna (Auxis thazard). The reproduction aspect observed in this study were: sex ratio, gonado-somatic index (GSI), gonad maturity level (GML), fecundity, and first length of maturity. The condition factor was also observed in this study. Sampling was carried out from November to December 2019 by collecting 84 individuals of Frigate Tuna fish. The result showed that the sex ratio between male and female showed balance condition with sex ratio value of 1:1.8. Analysis on the gonad showed that Gonado-somatic index (GSI) of male and female were were 0.0124 – 0.0308 % and 0.0142 – 0.0254 %, respectively. The fecundity of the fish was ranging from 106,430.6 to 518,843.9 eggs. The length of the first maturity for male and female was 337.716 ± .012 mm and 333.053 ± 0.009 mm, respectively. Total length of the fish was ranging from 317 to 405 mm, while the body weight was ranging from 414.27 to 854.52 gram.